KONSEP Al-ḤUBB AL-ILĀHĪ; STUDI ANALISIS TERHADAP PEMIKIRAN IBN ‘ARABĪ DALAM KITAB AL-FUTŪḤĀ AL-MAKKIYYAH - Nihayatul Husna (Wahana Islamika: Jurnal Studi Keislaman, 2022)
Abtract : This study focuses on analyzing the term of ḥubb in the Al-Futūḥāt Al-Makkiyyah. This is crucial term because in the perspective of Ibn ‘Arabī, ḥubb is an maqām ilāhi which is not limited material things. According to him, love of God (al-ḥubb al-ilāhī) requires two foundations of love, namely; natural love (al-ḥubb aṭ-ṭabī’ī) and spiritual love (al-ḥubb ar-rūḥānī). The purpose of this study was to find the meaning of al-ḥubb al-ilāhi in the perspective of Ibn ‘Arabī. The research method employs library research by constructing al-Futūḥāt al-Makkiyyah by Ibn ‘Arabī as the object of study. Starting with tracing all the term ḥubb in the Al-Futūḥāt Al-Makkiyyah as seminal concept, conducting language studies, mapping out the interpretations, and reviewing the result of studies, then formulating concept related to the issues being raised. This study reveal four important points of the concept of al-ḥubb al-ilāhi from the perspective of Ibn ‘Arabī, namely ḥubb as the cause of the existence of the universe, māqāmat ḥubb, three forms of ḥubb, conditions of al-ḥubb al-ilāhi. These four points in addition to describing the concept of al-ḥubb al-ilāhi Ibn ‘Arabī also provide a new understanding of the meaning of the word ḥubb which has undergone a change in conceptual meaning. When mentioning the word ḥubb, what appears is an understanding that refers to the form of obedience to Allah and His Messenger.